Life after life : a novel - Atkinson, Kate (New York : Reagan Arthur Books/Little, Brown and Company, 2013)
What if you could live again and again, until you got it right? On a cold and snowy night in 1910, Ursula Todd is born to an English banker and his wife. She dies before she can draw her first breath. On that same cold and snowy night, Ursula Todd is born, lets out a lusty wail, and embarks upon a life that will be, to say the least, unusual. For as she grows, she also dies, repeatedly, in a variety of ways, while the young century marches on towards its second cataclysmic world war. Does Ursula's apparently infinite number of lives give her the power to save the world from its inevitable destiny? And if she can -- will she? Darkly comic, startlingly poignant, and utterly original -- this is Kate Atkinson at her absolute best.
Keywords: Reincarnation -- Fiction; Fantasy fiction